Strategies on improvement of pigment formation and reduction of citrinin in Monascus fermentation. (28th September 2022) - Mou, Lu; Pan, Runze; Jiang, Wankui; Zhang, Wenming; Xin, Fengxue; Jiang, Yujia; Jiang, Min
Abstract: Monasucs pigments, as natural food colorants, have worldwide popularity owing to their antibacterial ability and superior coloring characteristics, as well as various applications in food, medicine, cosmetics and several other fields. Therefore, there is a considerable demand of pigments and various approaches have been conducted to improve pigment production. However, citrinin, which causes great harm to human health, is undesirably generated during the fermentation. Thus, great efforts have been made to increase pigment production and decrease citrinin formation by culture media and condition optimization, mutation breeding or genetic engineering. For the purpose of giving insight for further research, this article makes a summary of existing study advances in Monasucs pigment production. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.